Rationale and design of the randomised, controlled Percutaneous coronary intervention using Assisted Robotic TechnologY (PARTY) trial - Rohan Rajaratnam; Craig Juergens; Sidney T Lo; Dominic Y Leung; John K French; James Xu; James Leung; Hashim Kachwalla; Krishna Kaddapu; Tamer Badie; Christian Mussap (Open Heart)
Introduction Percutaneous coronary intervention (PCI) is performed by interventional cardiologists who, over their career, are exposed to substantial X-ray radiation and also face potential musculoskeletal injuries from the prolonged wearing of heavy protective equipment. Patients are also at risk from radiation exposure. Robotic-assisted PCI (R-PCI) allows millimetre control of the coronary guide-catheter, guidewires and intracoronary devices via three joysticks and touchscreens located within in a shielded ‘cockpit’, away from radiation. Initial studies have demonstrated efficacy and safety of R-PCI with significant radiation reductions. However, these studies are non-randomised, registry based or observational data with short clinical follow-up. We aim to perform the first randomised controlled trial investigating R-PCI compared with manual PCI (M-PCI) with longer clinical follow-up.Methods and analysis The Percutaneous coronary intervention using Assisted Robotic TechnologY (PARTY) trial is a single-centre, prospective, randomised, open-label clinical trial comparing R-PCI to M-PCI. Eligible patients between 18 and 85 years undergoing coronary angiography, and are subsequently deemed to require PCI, will be screened. A key exclusion criterion is if the operator determines that the participant or coronary anatomy is unsuitable for R-PCI. Patients will be randomised to R-PCI or M-PCI in a 1:1 fashion. The primary outcome is radiation exposure to the patient, as measured by personal radiation dosimeters. Other procedural, safety and efficacy outcomes will be compared. Patients will be followed up until hospital discharge (or 72 hours, whichever occurs first), and then by telephone at 30 and 365 days.Trial registration number ACTRN12623000480684.